Impact of Subclinical Borderline Inflammation on Kidney Transplant Outcomes. Issue 2 (February 2021) - Seifert, Michael E.; Agarwal, Gaurav; Bernard, Miriam; Kasik, Ellen; Raza, S. Sikandar; Fatima, Huma; Gaston, Robert S.; Hauptfeld-Dolejsek, Vera; Julian, Bruce A.; Kew, Clifton E.; Kumar, Vineeta; Mehta, Shikha; et al.
Abstract : Background: Surveillance biopsies permit early detection of subclinical inflammation before clinical dysfunction, but the impact of detecting early subclinical phenotypes remains unclear. Methods: We conducted a single-center retrospective cohort study of 441 consecutive kidney transplant recipients between 2015 and 2018 with surveillance biopsies at 6 months post-transplant. We tested the hypothesis that early subclinical inflammation (subclinical borderline changes, T cell-mediated rejection, or microvascular injury) is associated with increased incidence of a composite endpoint including acute rejection and allograft failure. Results: Using contemporaneous Banff criteria, we detected subclinical inflammation in 31%, with the majority (75%) having a subclinical borderline phenotype (at least minimal inflammation with mild tubulitis [>i0t1]). Overall, subclinical inflammation was independently associated with the composite endpoint (adjusted hazard ratio, 2.88; 1.11-7.51; P  = 0.03). The subgroup with subclinical borderline inflammation, predominantly those meeting the Banff 2019 i1t1 threshold, was independently associated with 5-fold increased hazard for the composite endpoint ( P  = 0.02). Those with concurrent subclinical inflammation and subclinical chronic allograft injury had worse outcomes. The effect of treating subclinical inflammation was difficult to ascertain in small heterogeneous subgroups. Conclusions: Subclinical acute and chronic inflammation are common at 6 months post-transplant in kidney recipients with stable allograft function. The subclinical borderline phenotype with both tubulitis and interstitial inflammation was independently associated with poor long-term outcomes. Further studies are needed to elucidate the role of surveillance biopsies for management of allograft inflammation in kidney transplantation. Abstract : Supplemental Digital Content is available in the text.